Influence Leverage And Profitability To Company Values With Sustainability Report As Intervening Variable ( Study Empirical In the Company Sector Infrastructure Listed on the Indonesia Stock Exchange in 2020-2023) - Livitri Sri Yunita Sari; Ratih Kusumastuti; Muhammad Gowon (CV. AFDIFAL MAJU BERKAH, 2025)
This study was conducted to determine the effect of leverage, profitability, on firm value mediated by sustainability reports. This study uses secondary data taken directly from the financial statements and annual reports of Infrastructure Sector Companies listed on the Indonesia Stock Exchange in 2020-2023. This study uses the Smart-PLS application with results showing that leverage has a positive effect on firm value, profitability has no effect on firm value, leverage has no effect on sustainability reports, profitability has no effect on sustainability reports, sustainability reports have no effect on firm value, institutional ownership has no effect on firm value, and leverage and profitability mediated by sustainability reports have no effect on firm value.